Steel with excellent surface quality for power battery shell and manufacturing method thereof
Through fine control of chemical composition and process optimization, the performance and cost of existing battery shell steel is solved, and steel for power battery shell with excellent surface quality and comprehensive mechanical properties is produced, meeting the market's high-performance and low-cost materials demand.
Patent Information
- Application Number
- CN202411549186.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art battery shell steel has shortcomings in production process, cost, performance, etc., and it is difficult to meet the market's demand for high-performance and low-cost power battery shell steel.
By precisely controlling the chemical composition in the steel and combining the optimization of smelting, hot rolling, acid rolling, annealing, leveling and other processes, a power battery shell steel with excellent surface quality and comprehensive mechanical properties is produced.
The high yield strength, tensile strength, elongation and surface quality of steel has been improved, and the requirements of power battery shells for high strength, high elongation and excellent stamping performance are met, while ensuring corrosion resistance in long-term use and Security.
Smart Images

Figure BDA0005114617790000071 
Figure BDA0005114617790000072 
Figure BDA0005114617790000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metallurgy, and in particular to a steel for a power battery casing with excellent surface quality and a manufacturing method thereof. Background Art
[0002] With the booming global energy storage market, cylindrical batteries have been widely used in power tools, laptops, electric vehicles and other fields due to their process maturity, highly automated production level, excellent pressure resistance and product consistency. In particular, the 18650 battery, whose shell stamping speed can reach 140 per minute, is packaged and used after cleaning and nickel electroplating, becoming an important part of the power battery market. As a product directly facing end users, power batteries are subject to strict requirements on safety and appearance quality. Therefore, in the production process of steel for power battery shells, the process factors that affect the safety and appearance of the battery shell must be strictly controlled.
[0003] At present, there are many patent reports in the field of battery shell steel in China. For example, patent CN1174109C reports an ultra-thin steel strip for battery shell and its production method, the weight percentage of its chemical composition is: C≤0.0050%, Si≤0.020%, Mn: 0.15~0.30%, P: 0.010%~0.030%, S: ≤0.015%, N≤0.0040%, Al: 0.020%~0.07%, Ti: 0.010%~0.030%, Nb: 0.010%~0.025%, the balance is Fe, the patent is ultra-low carbon composition, the pressure resistance is weak, and mainly by adding Ti and Nb elements to obtain good stamping performance, the cost is high, and at the same time, the single-stand rolling will have a large difference in thickness between the head and the tail, which needs to be cut, resulting in a low yield rate.
[0004] Patent CN100560770C reports a battery shell steel with excellent planar isotropy and a manufacturing method thereof. The chemical composition weight percentage of the battery shell steel is as follows: C: 0.01% to 0.05%, Si≤0.03%, Mn: 0.10% to 0.50%, P≤0.020%, S≤0.015%, Als: 0.010% to 0.10%, N: 0.0020% to 0.0070%, Ti: 0.0050% to 0.020%, and the rest is Fe and unavoidable impurities. Its production steps include molten iron pretreatment, converter smelting, furnace refining, hot rolling, pickling, cold rolling, hood annealing, leveling, and finishing into finished coils. This patent is mainly for the situation that the performance fluctuations at the head and tail are large through hood annealing.
[0005] Patent CN102286699B reports a rapid stamping steel for battery shells and a preparation method. The chemical composition weight percentage of the battery shell steel is as follows: C: 0.0001%~0.005%, Mn: 0.10%~0.20%, Al: 0.010%~0.050%, N: 0.00010%~0.0040%, Nb: 0.010%~0.030%, and P≤0.020%, S≤0.0150%, Cu≤0.050%, Ni≤0.050%, Cr≤0.080%, Mo≤0.050%, Si≤0.02%, and the rest is Fe and unavoidable impurities. Production steps: smelting and continuous casting into billets according to the pure steel process; heating of continuous casting billets; rough rolling; finishing rolling in the single-phase austenite zone; coiling; pickling; cold rolling; degreasing; annealing in a full hydrogen bell furnace; leveling and standby. This patent belongs to the Nb-IF steel system, which has a high cost. Conventional bell annealing is used, and the performance of the coil fluctuates greatly. It adopts an ultra-low C and low Mn component system design, and the final yield strength is low and does not have compressive resistance.
[0006] In addition, patent CN106148803A discloses a method for producing steel for deep-drawn battery shells, but it only introduces the hot rolling process and does not involve the cold rolling process, so the comprehensive performance of its products may be subject to certain limitations.
[0007] In summary, the existing battery shell steel has various deficiencies in production process, cost, performance, etc., and it is difficult to meet the market demand for high-performance, low-cost power battery shell steel. Therefore, developing a new type of power battery shell steel and its manufacturing method to improve the yield strength, tensile strength, elongation and surface quality of the product has become an urgent problem to be solved. Summary of the invention
[0008] In view of the technical deficiencies of existing products, the present invention proposes a power battery shell steel with excellent surface quality and a manufacturing method thereof. The power battery shell steel has a yield strength of 190MPa-260MPa, a tensile strength of 320MPa-390MPa, an elongation of ≥38%, a hardness HR30T range of 45-50, 0.5μm≤Ra≤1.0μm, and a peak number RP C ≥120, and high-speed stamping can be achieved in the end, while the steel shell has good pressure resistance and excellent surface quality.
[0009] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:
[0010] On the one hand, the present invention provides a steel for a power battery casing with excellent surface quality, the chemical composition of the steel for a power battery casing being as follows by weight percentage: C: 0.015% to 0.025%, Si≤0.030%, Mn: 0.10% to 0.20%, 0.01%≤P≤0.02%, S≤0.012%, Cr: 0.03 to 0.08%, Alt: 0.02% to 0.05%, B: 0.002 to 0.005%, and the rest being Fe and unavoidable impurities.
[0011] As a further optimization scheme of the present invention, the steel for the power battery casing meets the following properties: yield strength of 190MPa~260MPa, tensile strength of 320MPa~390MPa, elongation ≥38%, HR30T range of 45~50, 0.5μm≤Ra≤1.0μm, and RPC≥120.
[0012] On the other hand, the present invention provides a method for manufacturing steel for power battery casing with excellent surface quality, comprising the following steps: molten iron smelting, slab continuous casting, flame cleaning, soaking in a soaking furnace, hot rolling, layer cooling, coiling, pickling, cold rolling, continuous annealing, and flattening.
[0013] As a further optimization scheme of the present invention, in the smelting and continuous casting process: pre-slag removal and post-slag removal measures are taken during the molten iron pretreatment process to adjust the S element; self-circulating scrap steel is added in the early and middle stages of decarburization to modify the ladle top slag.
[0014] As a further optimization scheme of the present invention, during hot rolling: the heating temperature is controlled at 1200°C to 1250°C, and the final rolling temperature is 850°C to 890°C.
[0015] As a further optimization scheme of the present invention, in the layer cooling process: by controlling the layer cooling process, a segmented cooling process is realized, the first 20 meters are concentratedly cooled to cool the steel coil to 710℃~750℃, the middle section 60 meters are slowly cooled to 680℃~710℃, and the last 20 meters are concentratedly cooled again to cool the steel coil to 600℃~650℃, and the cooling process is set to be "n" type.
[0016] As a further optimization scheme of the present invention, in the coiling process: the final coiling temperature is set to 600°C to 650°C.
[0017] As a further optimization scheme of the present invention, in the cold rolling process: the cold rolling adopts five-stand continuous rolling, the cold rolling reduction rate is ≥85%, the smooth roller rolling is adopted in the last stand, the roughness is controlled to be ≤0.5μm, and RPc≥220.
[0018] As a further optimization scheme of the present invention, in the continuous annealing process: the annealing temperature is 740°C to 760°C, the speed of the strip in the furnace is 200mpm to 250mpm, and the rapid cooling section uses air cooling to accelerate the cooling speed by 30°C / s to 50°C / s, cooling from 680°C to 690°C to 340°C to 350°C, and then heating the strip in the furnace to heat it to 400°C to 410°C.
[0019] As a further optimization scheme of the present invention, in the leveling process: a laser texturing roller is used for leveling, the leveling elongation is controlled at 1.0-1.5%, and a leveling roller with Ra of 1.6 μm is used to ensure that the board surface roughness is 0.5 μm≤Ra≤1.0 μm, and RPc≥120.
[0020] The role of the alloying elements in the steel grades in the present invention is mainly based on the following principles:
[0021] Carbon (C): trace C elements help to improve the strength and hardness of steel, ensuring that the battery shell is not easily deformed. However, with the increase of C elements, the elongation of the steel plate will decrease, affecting the stamping performance of the battery shell steel. Therefore, the present invention adopts a low-carbon component design, controlling C: 0.015% to 0.025%.
[0022] Silicon (Si): If the Si content is too high, the iron oxide scale on the surface of the steel plate is difficult to remove, and micro cracks are easily formed on the surface due to the intrusion of oxides. During the high-speed deep drawing process of the steel strip, the micro cracks can serve as crack sources and cause the steel plate to crack. In addition, if the Si content is too high, it will affect the electroplating performance of the steel plate. Therefore, in the present invention, Si≤0.030%.
[0023] Manganese (Mn): Mn can reduce the phase transition temperature from austenite to ferrite (which can compensate for the increase in the phase transition temperature from austenite to ferrite caused by the reduction in the C element content), expand the hot working temperature range, and is beneficial to refining the ferrite grain size; but if the Mn content is too high, it will be detrimental to the plasticity, stamping performance, and fatigue performance. Taking all factors into consideration, the Mn percentage control range in the present invention is 0.10% to 0.20%.
[0024] Phosphorus (P): A certain amount of P content in steel has a certain corrosion resistance effect, but excessive P is easy to form segregation in steel, which is not good for the formability of steel plates. Therefore, the content of P element in the present invention is controlled in the range of 0.01% to 0.02%.
[0025] Sulfur (S): S is a harmful element in battery shell steel, which makes the steel hot brittle, reduces the ductility and toughness of the steel, and easily causes cracks during rolling. In addition, S is not good for welding performance and reduces corrosion resistance. Therefore, the present invention tries to control the S content in the steel within the range of S≤0.012%.
[0026] Chromium (Cr): A small amount of Cr in steel improves the corrosion resistance of the steel, and Cr also helps to improve the adhesion of the nickel layer. When Cu and Cr are added to the steel at the same time, the electrochemical reaction in the steel is inhibited, which helps to improve the corrosion resistance of the battery shell. However, Cr can significantly improve the strength and hardness of the steel and deteriorate the stamping performance of the steel plate. Therefore, the Cr element is controlled in the range of 0.03-0.08%.
[0027] Aluminum (Alt): Al is mainly added as a deoxidizer in steelmaking. A small amount of Al reacts with N in steel to produce AlN, which can weaken the effect of solid solution N, improve the anti-aging effect, and play a pinning role to refine the grains. However, excessive Al will cause the precipitate to aggregate, and "sand hole" defects are prone to occur during stamping overcharging. Therefore, the Alt content is controlled at 0.02% to 0.05%.
[0028] Boron (B): The B element plays a role in fixing nitrogen in steel, weakening the aging effect of nitrogen on the steel plate. At the same time, BN can refine the grains and strengthen the steel through precipitation. However, too high a content of the B element will lead to a decrease in the plasticity and toughness of the steel plate, affecting the service performance of the final battery casing. Therefore, the control range of the B element is 0.002% to 0.005%.
[0029] The manufacturing method of the cold-rolled sheet for the ultra-low carbon battery shell requires the following steps: molten iron smelting, slab continuous casting, flame cleaning, soaking in a soaking furnace, hot rolling, layer cooling, coiling, pickling, cold rolling, continuous annealing, and leveling. Its process features are as follows:
[0030] Smelting and continuous casting: In the process of molten iron pretreatment, taking measures such as pre-slag removal and post-slag removal to adjust the [S] element can reduce harmful elements in molten steel. Adding self-circulating scrap steel in the early and middle stages of decarburization to modify the ladle top slag can help reduce impurity elements in molten steel.
[0031] Hot rolling: The heating temperature is controlled at 1200℃~1250℃. At high temperature, the second phase particles are dissolved in the steel, which is beneficial to rolling. Fine particles are re-precipitated during the coiling process, which is beneficial to improving the stamping performance and corrosion resistance of the material. The final rolling temperature is controlled at 850℃~890℃, which can ensure that the final rolling temperature is controlled above the austenite temperature to avoid the mixed crystal phenomenon caused by rolling in the two-phase region.
[0032] Layer cooling and coiling: By controlling the layer cooling process, a segmented cooling process is realized. The first 20 meters are concentratedly cooled to cool the steel coil to 710℃~750℃, the middle section 60 meters are slowly cooled to 680℃~710℃, and the last 20 meters are concentratedly cooled to cool the steel coil to 600℃~650℃. The cooling process is set in an "n" shape. This process is conducive to minimizing the performance of hot coils while ensuring excellent surface quality. The final coiling temperature is set to 600℃~650℃.
[0033] Pickling and cold rolling: Cold rolling adopts five-stand continuous rolling, and the cold rolling reduction rate is ≥85%. A large reduction rate can increase the grain distortion energy in the steel, reduce the recrystallization temperature, and is conducive to grain refinement and improving the deep drawing performance of the steel plate. The last stand adopts smooth roller rolling, and the roughness is controlled to be ≤0.5μm, RPc≥220. This measure can effectively improve the surface quality of the finished plate and improve the adhesion of the steel plate.
[0034] Continuous annealing: annealing temperature 740℃~760℃, strip speed in furnace: 200mpm~250mpm, rapid cooling section uses air cooling to accelerate the cooling speed: 30℃ / s~50℃ / s, cooling from 680℃~690℃ to 340℃~350℃. Then through furnace heating, the temperature of the strip is heated to 400℃~410℃ to improve the anti-aging effect of the steel grade.
[0035] Smoothing: Use laser texturing roller for smoothing, the smoothing elongation is controlled at 1.0-1.5%, and a smoothing roller with Ra of 1.6μm is used to ensure that the plate surface roughness is 0.5μm≤Ra≤1.0μm, and the peak number RPc≥120. This roughness is conducive to the smooth surface of the battery shell after stamping.
[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0037] The present invention mainly produces a steel for power battery shell with excellent surface quality and comprehensive mechanical properties by precisely controlling the chemical composition of the steel and optimizing the processes of smelting, hot rolling, acid rolling, annealing, flattening, etc. This steel not only meets the requirements of power battery shell for high strength, high elongation and excellent stamping performance, but also ensures the corrosion resistance and safety of the battery shell in long-term use.
[0038] Performance improvement brought by fine control of chemical composition: Balanced control of carbon (C): The present invention controls the carbon content between 0.015% and 0.025%. This range not only ensures the necessary strength and deformation resistance of the steel, but also minimizes the aging sensitivity, so that the steel can maintain stable mechanical properties during long-term use. Restrictions on silicon (Si), phosphorus (P) and sulfur (S): By strictly controlling the content of silicon, phosphorus and sulfur (Si≤0.030%, P≤0.02%, S≤0.012%), surface defects are reduced, electroplating quality is improved, hot brittleness is reduced and ductility is improved, thereby ensuring the stability and reliability of the steel during stamping and electroplating. Optimization of manganese (Mn): The manganese content is controlled between 0.10% and 0.20%. This range not only ensures the strength, plasticity and hot working properties of the steel, but also reduces the risk of mixed crystals, so that the steel can maintain a uniform grain structure during hot rolling and cold rolling. Addition of specific elements: The present invention also adds appropriate amounts of elements such as chromium (Cr) and aluminum (Alt), as well as a trace amount of boron (B). These elements work together in the steel to improve the corrosion resistance and aging resistance of the steel, while meeting the requirements for tensile strength and yield strength.
[0039] The optimization of production process brings about the improvement of efficiency and quality: Hot metal pretreatment and continuous casting: Through fine front and rear slag removal and ladle top slag modification, the harmful element content is significantly reduced, providing a pure substrate foundation for subsequent processes. Hot rolling: The heating temperature is controlled at 1200℃~1250℃ to ensure that the second phase particles are dissolved in the steel at high temperature, which is conducive to rolling, and fine particles are re-precipitated during the coiling process; the final rolling temperature is controlled at 850℃~890℃ to avoid the mixed crystal phenomenon caused by rolling in the two-phase zone. Layer cooling and coiling: The segmented cooling process is adopted to form an "n"-shaped cooling curve, with concentrated cooling in the front section, slow cooling in the middle, and concentrated cooling in the back section. It can ensure that the hot coil performance is minimized while ensuring excellent surface quality and stamping performance. The coiling temperature is set at 600℃~650℃, which is conducive to obtaining ideal organizational structure and performance. Pickling cold rolling: The application of five-stand continuous rolling and large reduction rate, combined with smooth roller rolling, not only improves the surface quality, but also facilitates the recrystallization of grains in the subsequent annealing process, thereby improving the mechanical properties and stamping properties of the steel. Continuous annealing: The precisely controlled annealing temperature and cooling rate ensure the full precipitation of the second phase and the complete growth of the grains, significantly improving the mechanical properties of the finished product. Flattening: The use of laser texturing and strictly controlled roughness further improves the surface quality and electroplating adhesion of the plate, so that the final product can meet the surface finish and corrosion resistance requirements of the power battery shell.
[0040] In summary, the present invention has achieved innovative development of steel for power battery casings through well-designed chemical composition and meticulous manufacturing process. This steel not only has excellent surface quality and comprehensive mechanical properties, but also exhibits excellent anti-aging performance. Its successful development has solved key problems in the industry and provided a more reliable material choice for the production of power battery casings. At the same time, the implementation of the present invention has also promoted the progress and innovative development of metallurgical technology, bringing significant economic and social benefits to related industries. DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.
[0042] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0043] The present invention is further described in detail below in conjunction with specific embodiments.
[0044] The chemical composition and content of the molten steel of Examples 1-6 of the present invention and Comparative Examples 1-7 are shown in Table 1, and the rest are Fe and unavoidable impurity elements.
[0045] Table 1 Chemical composition, wt%
[0046] category C Si Mn P S Cr Alt B Example 1 0.025 0.021 0.19 0.018 0.004 0.066 0.028 0.0050 Example 2 0.015 0.012 0.12 0.014 0.012 0.043 0.030 0.0030 Example 3 0.020 0.011 0.15 0.015 0.006 0.035 0.022 0.0022 Example 4 0.019 0.028 0.13 0.012 0.010 0.036 0.026 0.0035 Example 5 0.022 0.007 0.12 0.010 0.009 0.052 0.036 0.0043 Example 6 0.024 0.004 0.17 0.013 0.005 0.045 0.027 0.0034 Comparative Example 1 0.0030 0.023 0.12 0.010 0.008 - 0.012 0.0045 Comparative Example 2 0.0021 0.018 0.20 0.006 0.004 - 0.075 - Comparative Example 3 0.023 0.023 0.15 0.012 0.005 0.125 0.066 - Comparative Example 4 0.047 0.007 0.22 0.015 0.005 - 0.063 - Comparative Example 5 0.025 0.018 0.18 0.012 0.007 - - - Comparative Example 6 0.042 0.006 0.21 0.011 0.005 - - 0.0052 Comparative Example 7 0.051 0.012 0.32 0.012 0.007 0.049 0.054 0.0046
[0047] All production processes were trial-produced according to Table 2, and the finished product thickness specification was 0.30 mm.
[0048] The manufacturing method of steel for power battery casing includes the following steps: molten iron smelting, slab continuous casting, flame cleaning, soaking in a soaking furnace, hot rolling, layer cooling, coiling, pickling, cold rolling, continuous annealing, and leveling.
[0049] In the smelting and continuous casting process: in the process of molten iron pretreatment, pre-slag removal and post-slag removal measures are taken to adjust the S element; self-circulating scrap steel is added in the early and middle stages of decarburization to modify the ladle top slag.
[0050] In the hot rolling process: the heating temperature is controlled at 1200℃~1250℃, and the final rolling temperature is 850℃~890℃.
[0051] In the layer cooling process: by controlling the layer cooling process, the segmented cooling process is realized. The first 20 meters are concentratedly cooled to cool the steel coil to 710℃~750℃, the middle section 60 meters are slowly cooled to 680℃~710℃, and the last 20 meters are concentratedly cooled again to cool the steel coil to 600℃~650℃. The cooling process is set into an "n" shape.
[0052] In the coiling process: the final coiling temperature is set at 600℃~650℃.
[0053] In the cold rolling process: five-stand continuous rolling is adopted for cold rolling, the cold rolling reduction rate is ≥85%, smooth roller rolling is adopted in the last stand, the roughness is controlled to be ≤0.5μm, and RPc≥220.
[0054] In the continuous annealing process: the annealing temperature is 740℃~760℃, the strip speed in the furnace is 200mpm~250mpm, and the fast cooling section uses air cooling to accelerate the cooling speed by 30℃ / s~50℃ / s, cooling from 680℃~690℃ to 340℃~350℃, and then heating the strip in the furnace to 400℃~410℃.
[0055] In the leveling process: laser texturing roller is used for leveling, the leveling elongation is controlled at 1.0-1.5%, and a leveling roller with Ra of 1.6μm is used to ensure that the board surface roughness is 0.5μm≤Ra≤1.0μm, RPc≥120.
[0056] The production processes of molten steel of Examples 1-6 of the present invention and Comparative Examples 1 to 7 are shown in Table 2, wherein Comparative Examples 1 to 7 are not smelted completely according to the production process of the present invention.
[0057] Table 2 Production process
[0058]
[0059] The mechanical properties and surface quality of the final product are shown in Table 3.
[0060] Table 3 Detection performance values
[0061]
[0062]
[0063] All properties of Examples 1 to 6 can meet the requirements. Comparative Examples 1 and 2 have ultra-low carbon components, and the final mechanical properties and hardness cannot meet the requirements. Comparative Example 3 uses low-temperature coiling, which leads to high mechanical properties and low elongation of the final product, which does not meet the requirements. Comparative Example 4 has high strength and low elongation due to the low annealing temperature, which does not meet the requirements of high-speed stamping. Comparative Examples 5 and 6 use rear-stage cooling and the coiling temperature is high, resulting in poor surface quality of the finished product, oxygen compression stripes, and low hardness. Comparative Example 7 uses low-temperature annealing, and the performance is high, which does not meet the requirements of high-speed stamping. In addition, no Cr element is added to Comparative Examples 1, 2, 4, 5, and 6. In the laboratory high-temperature simulation test, the grain size grows significantly. No B element is added to Comparative Examples 2, 3, 4, and 5. When the steel coil is placed for more than 3 months, stripes are prone to appear during the stamping process.
[0064] The above description only provides a specific exemplary description of the present invention. It should be noted that the specific implementation of the present invention is not limited to the above method. As long as various non-substantial improvements are made using the technical concept and technical solution of the present invention, or the technical concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A steel for power battery casing with excellent surface quality, characterized in that: The chemical composition of the steel for the power battery casing is calculated by weight percentage as follows: C: 0.015% to 0.025%, Si≤0.030%, Mn: 0.10% to 0.20%, 0.01%≤P≤0.02%, S≤0.012%, Cr: 0.03% to 0.08%, Alt: 0.02% to 0.05%, B: 0.002 to 0.005%, and the rest is Fe and unavoidable impurities.
2. The steel for power battery casing with excellent surface quality according to claim 1, characterized in that: The steel for power battery housing meets the following properties: yield strength 190MPa-260MPa, tensile strength 320MPa-390MPa, elongation ≥38%, HR30T range 45-50, 0.5μm≤Ra≤1.0μm, RP C ≥120.
3. A method for manufacturing steel for power battery casing with excellent surface quality as claimed in claim 1 or 2, characterized in that: The process comprises the following steps: molten iron smelting, slab continuous casting, flame cleaning, soaking in a soaking furnace, hot rolling, layer cooling, coiling, pickling, cold rolling, continuous annealing and leveling.
4. The method for manufacturing steel for power battery casing with excellent surface quality according to claim 3, characterized in that: In the smelting and continuous casting process: in the process of molten iron pretreatment, pre-slag removal and post-slag removal measures are taken to adjust the S element; self-circulating scrap steel is added in the early and middle stages of decarburization to modify the ladle top slag.
5. The method for manufacturing steel for power battery casing with excellent surface quality according to claim 3, characterized in that: During hot rolling: the heating temperature is controlled at 1200℃~1250℃, and the final rolling temperature is 850℃~890℃.
6. The method for manufacturing steel for power battery casing with excellent surface quality according to claim 3, characterized in that: In the layer cooling process: by controlling the layer cooling process, a segmented cooling process is realized. The first 20 meters are concentratedly cooled to cool the steel coil to 710℃~750℃, the middle section 60 meters are slowly cooled to 680℃~710℃, and the last 20 meters are concentratedly cooled again to cool the steel coil to 600℃~650℃. The cooling process is set into an "n" shape.
7. The method for manufacturing steel for power battery casing with excellent surface quality according to claim 3 or 6, characterized in that: In the coiling process: the final coiling temperature is set at 600℃~650℃.
8. The method for manufacturing steel for power battery casing with excellent surface quality according to claim 3, characterized in that: In the cold rolling process: five-stand continuous rolling is adopted for cold rolling, the cold rolling reduction rate is ≥85%, smooth roller rolling is adopted in the last stand, the roughness is controlled to be ≤0.5μm, and RPc≥220.
9. The method for manufacturing steel for power battery casing with excellent surface quality according to claim 3, characterized in that: In the continuous annealing process: the annealing temperature is 740℃~760℃, the strip speed in the furnace is 200mpm~250mpm, and the fast cooling section uses air cooling to accelerate the cooling speed by 30℃ / s~50℃ / s, cooling from 680℃~690℃ to 340℃~350℃, and then heating the strip in the furnace to 400℃~410℃.
10. The method for manufacturing steel for power battery casing with excellent surface quality according to claim 3, characterized in that: In the leveling process: laser texturing roller is used for leveling, the leveling elongation is controlled at 1.0-1.5%, and a leveling roller with Ra of 1.6μm is used to ensure that the board surface roughness is 0.5μm≤Ra≤1.0μm, RPc≥120.
Citation Information
Patent Citations
Steel for battery shell with excellent planar isotropism and its production
CN100560770C
Corrosion-resistant steel with impact molding rate not smaller than 150 per minute for cell shell and preparation method thereof
CN102286699B
Production method for steel for deep drawing of battery case
CN106148803A
Cited By
Hot-press forming ultrahigh-strength steel for battery shell and preparation method of hot-press forming ultrahigh-strength steel
CN121674847A
A hot-pressed ultra-high strength steel for battery casing and its preparation method
CN121674847B